Vulnerable plaques in atherosclerosis: focus on angiogenesis-associated phenotypic crosstalk - Hou, Xin-Zheng; Yang, Ying-Tian; Yao, Jian-Ming (Frontiers in Pharmacology, 2026)
Atherosclerosis (AS) constitutes a major cardiovascular disorder posing a severe threat to human health, with the rupture of vulnerable plaques marking a critical turning point in the progression of AS. This pathological event can trigger acute myocardial infarction and stroke, thereby exerting a profound adverse impact on patient prognosis. In contrast to normal arterial tissues, vulnerable plaques are characterized by an abundance of neovascularization, which is generated through angiogenic pathways. Although these neovessels serve to alleviate the hypoxic microenvironment within the plaque, they concurrently compromise plaque stability. Notably, angiogenesis engages in crosstalk with AS-associated phenotypic processes, including cellular apoptosis, extracellular matrix remodeling, inflammatory responses, and oxidative stress. This interplay forms a positive feedback loop that further exacerbates the destabilization of vulnerable plaques. The vascular endothelial growth factor (VEGF) pathway plays a central regulatory role in angiogenesis. Targeting the VEGF pathway to inhibit angiogenesis and enhance plaque stability has thus opened a novel therapeutic avenue for AS management. In comparison, this strategy has demonstrated promising efficacy in preclinical studies; however, a lack of safe and reliable pharmaceutical agents remains, hindering their translation into clinical practice for AS treatment. In this review, the authors summarize the underlying mechanisms governing angiogenesis and vulnerable plaque formation, and further explore the phenotypic crosstalk between these processes. The ultimate aim is to provide valuable insights to facilitate future breakthroughs in the development of therapeutic strategies for AS.